Pengaruh Label halal dan Celebrity Endorser Terhadap Keputusan Pembelian Produk Make Over di MK Cosmetic Tanjungpinang - Dewi Maharani; Aulia Rahman; Hanafi Yunus (EMASHA: Jurnal Ekonomi, Manajemen dan Akuntansi Syariah, 2025)
This study aims to determine the effect of the halal label and celebrity endorsers on purchasing decisions for Make Over products at MK Cosmetic Tanjungpinang. The method used in this research is quantitative method. The population of this research is consumers of Make Over products at MK Cosmetic Tanjungpinang for the period December 2024 to April 2025, totaling 560 consumers. The sampling technique in this study used the calculation of the slovin formula with a sample size of 85 respondents. The data collection technique in this study used a questionnaire with Google Form. The results of this study indicate that the halal label variable has a positive and significant effect on purchasing decisions for Make Over products at MK Cosmetic Tanjungpinang with a significance value <0.05 (0.042 <0.05) and tcount> ttable (2.063>1.663). While the celebrity endorser variable has a positive and significant effect on purchasing decisions for Make Over products at MK Cosmetic Tanjungpinang with a significance value of <0.05 (0.000 <0.05) and tcount> table (6.498>1.663). Simultaneously the halal label variable and celebrity endorser together have a positive and significant influence on purchasing decisions for Make Over products at MK Cosmetic Tanjungpinang with a significance level <0.05 (0.000 <0.05). The coefficient of determination is 0.683, which means that 68.3% of purchasing decisions are influenced by halal labels and celebrity endorsers. While the remaining 31.7% is influenced by variables.